Critical analysis of surgical treatment gastroduodenal ulcer - Piacenza, Guillermo; Czarnevicz, Daniel; Ferreira, Carlos (Cirugía del Uruguay, 1994)
Based on a study of 1.200 cases of gastroduodenal peptic u/cus (GDPU) treated with surgery, the authors evaluate and compare the results obtained with different surgical procedures. Three different groups were considered: resection procedures (649 patients, 54%), denervation procedures (257, 21,4%), and a group of "other procedures" (293 patients, 24,5%) including single e/asure and epipoplastia, direct hemostasis, and gastrojejunostomy. There was different morbility for each group: 26,4% for the resection one, 34,6% for denervation, and 28,8% far the other one; infectious complications were the most frequent in al/ groups. Ulcus recidive was 11,5% for denervation procedures and 2% for resections (p<0,05). Whi/e medica/ treatment failure seems to be the most importan/ risk factor for the first ones, urgent surgery is the most importan/ for resections. Mortality was 3, 6% for resections, 0% far denervations and 2,2% for the group of other procedures. The authors arrive to the conclusion that results of GDPU surgery in our environment can be compared to those of other centers. A correct evaluation of the patient is necessary for election of the procedure; risk factors are not determinant, only another element to be considered